HIPERINFLASI VENEZUELA: DAMPAKNYA TERHADAP POSISI STRATEGIS AMERIKA SERIKAT-VENEZUELA - Tegar Budisatria; Binsar Hamoraon Hasibuan; Rezha Hidayat Dwiputra (FISIP Universitas Tanjungpura, 2022)
This paper aims to describe the strategic position between the United States and Venezuela in the context of Venezuela's hyperinflation. Since 2016 Venezuela has experienced severe currency volatility and has become a backward country due to mismanagement of its economic policies. The occurrence of this phenomenon is known to have its roots in state takeovers of private companies in leading sectors and massive subsidies without a safety net during the oil price boom under Hugo Chavez's leadership. This instability was then inherited by his successor, Nicolas Maduro, which marked the weakening of the Venezuelan economy. Maduro initiated a policy of massive money printing and redenomination which in fact further increased domestic inflation. This is also directly proportional to the dynamics of the US-Venezuela relationship which started from the capitalist camp with the same pattern of interdependence. Over time, the spirit of Bolivarianism that strengthened in the Chavez and Maduro eras had a major impact on the relations between the two countries in terms of their strategic position. This of course has implications both at the level of ideology and trade between countries. This paper uses a qualitative-descriptive research method with literature study as a data source in describing the research problem. The researcher uses the theory of realism as an analytical lens and the conception of Bolivarianism which explains the behavior of Venezuela as a country overshadowed by a struggle for power.